Tracking the Loving Gaze. - Stylianou-Lambert, Theopisti; Panayides, Omiros (My University, 2020)
Tracking the Loving Gaze is a futile attempt to follow, map and capture the way cherished personal photographs are viewed. The authors asked 30 people to look at a preselected photograph that held a special meaning for them, while using an eye tracker. The raw visual data from this process—heat maps, focus maps and scan paths—became the foundation of a body of work that includes darkroom prints, short videos and a limited-edition artist book. Apart from exploring the invisible viewing processes of personal photography, this article introduces the concepts of the detached and the invested viewer, as well as the corresponding concepts of the cold and the loving gaze.
Keywords: Personal photography; Eye tracker; Book art; Loving gaze